Macrophage-based therapeutic strategies in glioblastoma: advancements in drug delivery and immunotherapy - Li, Dongyang; Zhang, Xinyue; Du, Yanwei (Frontiers in Oncology, 2026)
Glioblastoma (GBM) is a highly aggressive brain tumor, characterized by extensive infiltration, neovascularization, and resistance to conventional therapies. The unique tumor microenvironment (TME) of GBM is shaped by the blood-brain barrier (BBB), immune cells, and glioma-derived factors, complicating treatment efficacy. Macrophages, particularly tumor-associated macrophages (TAMs), play critical roles in GBM progression through immune evasion, angiogenesis, and therapeutic resistance. Advances in macrophage-based therapies, including engineered macrophages (CAR-M) and macrophage-mimetic nanoplatforms, offer promising strategies for targeted treatment. These approaches leverage macrophages’ natural ability to cross the BBB and selectively accumulate in tumors, enhancing therapeutic outcomes. This review highlights the roles of macrophages in the GBM TME, recent developments in macrophage-based drug delivery systems, and the potential of CAR-M therapies for improving GBM treatment efficacy.